2023
DOI: 10.3390/en16020812
|View full text |Cite
|
Sign up to set email alerts
|

Solar and Wind Energy Integrated System Frequency Control: A Critical Review on Recent Developments

Abstract: A paradigm shift in power systems is observed due to the massive integration of renewable energy sources (RESs) as distributed generators. Mainly, solar photovoltaic (PV) panels and wind generators are extensively integrated with the modern power system to facilitate green efforts in the electrical energy sector. However, integrating these RESs destabilizes the frequency of the modern power system. Hitherto, the frequency control has not drawn sufficient attention due to the reduced inertia and complex control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 211 publications
0
22
0
Order By: Relevance
“…This energy WSER must be equal to or greater than the residual from meeting the total energy demand with the help of conventional and solar power plants. As it seems from (18), WSER is a function of the ability of conventional stations and the power of PV facilities. This circumstance makes the analytical solution for the assessment of both power parameters (PV and grid generation) more difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This energy WSER must be equal to or greater than the residual from meeting the total energy demand with the help of conventional and solar power plants. As it seems from (18), WSER is a function of the ability of conventional stations and the power of PV facilities. This circumstance makes the analytical solution for the assessment of both power parameters (PV and grid generation) more difficult.…”
Section: Resultsmentioning
confidence: 99%
“…The AC frequency is becoming less stable, which is the second major problem caused by the widespread use of PV power stations in the domestic network. Due to numerous research works [18][19][20][21][22], the problem of frequency stability and control exists in large networks, including those with significant renewable generation, and it becomes especially urgent with the increasing portion of solar electricity. The lack of electromechanical inertia in PV facilities, which helps stabilize frequency in a grid and is an actual component of conventional generators in power stations, prevents the increase of solar electricity over some limit [23].…”
Section: Introductionmentioning
confidence: 99%
“…An active power reserve is generated by employing CPG control, as discussed in [38]. PV power can be summarised as follows by using CPG and is given by equation (33):…”
Section: Nomentioning
confidence: 99%
“…Moreover, some highly cited papers in the RES literature, such as Ratnam et al [5], Saha et al [11], Alam et al [12], Tróndheim et al [21], cite that the gearbox does not impose important issues in load flow and dynamic behaviour of the power system. Therefore, this item is not considered in the simulations of this work.…”
Section: Detailed Type 4 Wtgmentioning
confidence: 99%
“…Several researchers (e.g., [12][13][14][15][16][17][18][19][20]) observed that the increase in RES poses various challenges to the stability of power systems. The physical structure, mechanical characteristics, energy conversion mechanism, and control characteristics of power generators and equipment have a significant impact on the stability characteristics of traditional power systems based on SGs.…”
Section: Introductionmentioning
confidence: 99%